2021
DOI: 10.1177/15589447211014623
|View full text |Cite
|
Sign up to set email alerts
|

Hemi-hamate Arthroplasty for Base of Middle Phalanx Fracture: A Systematic Review

Abstract: Intra-articular fracture dislocations of the base of the middle phalanx are complex and debilitating injuries that present a management conundrum when nonreconstructable. Hemi-hamate arthroplasty (HHA) is a treatment modality of particular use in the setting of highly comminuted fractures. This systematic review aims to summarize the reported outcomes of HHA in this context. A literature search was conducted using MEDLINE, Embase, and PubMed, yielding 22 studies with 235 patients for inclusion. The weighted me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…Verdins et al 9 reported 2 of 11 patients who developed arthrosis of the PIPJ within 6 months of HHA and ultimately required a synthetic joint replacement. Although Calfee et al 13 reported loss of joint space in 43% of patients based on postoperative radiographic evaluation, these findings did not correlate with poorer 11 reported posttraumatic arthritis in 18% of cases. In addition, 12 studies found the weighted mean postoperation pain to be 1.0 (range, 0-2.0) using visual analog scale.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Verdins et al 9 reported 2 of 11 patients who developed arthrosis of the PIPJ within 6 months of HHA and ultimately required a synthetic joint replacement. Although Calfee et al 13 reported loss of joint space in 43% of patients based on postoperative radiographic evaluation, these findings did not correlate with poorer 11 reported posttraumatic arthritis in 18% of cases. In addition, 12 studies found the weighted mean postoperation pain to be 1.0 (range, 0-2.0) using visual analog scale.…”
Section: Discussionmentioning
confidence: 91%
“…[8][9][10]13,14,[17][18][19] The majority of these studies (4 of 7) report between 63 and 69 degrees arc of motion, similar to the average postoperative arc of motion (63 degrees) reported in our series (Table 4). Two systematic reviews reported an average postoperative PIPJ motion of 77 degrees (Frueh et al 4 ) and 74 degrees (Faulkner et al 11 ). The mean time to follow-up was 26 months in the current series, which is comparable to that reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations